PEMIMPIN VISIONER, PENDIDIKAN BERKUALITAS: ANALISIS PERAN KEPALA MADRASAH DI MA PERADABAN DUNIA - Yaqin, Muhammad (CV. AKIRA JAVA BULU, 2025)
This study aims to explore the role of the madrasah principal's leadership in improving the quality of education at MA Peradaban Dunia, a progressive Islamic educational institution under the auspices of the Baitul Kilmah Foundation, Bantul. Using a descriptive qualitative approach and case study method, data were obtained through in-depth interviews, direct observation, and documentation. The results of the study indicate that the visionary leadership of the madrasah principal is able to encourage curriculum innovation and adaptive learning strategies. The curriculum implemented is a combination of government standards and the institution's internal curriculum, which emphasizes the development of practical skills such as multimedia, journalism, Javanese script, and printing. Learning evaluation focuses more on output in the form of real student work rather than just academic grades. The success of this strategy can be seen from the increasing competitiveness of graduates who are able to continue their education to college and have entrepreneurial skills. Despite facing challenges such as student adaptation and the process of accepting new students, MA Peradaban Dunia remains consistent in developing a holistic and contextual education system. This study emphasizes the importance of the role of the madrasah principal as the main driver in educational transformation that is relevant to the needs of the times.